Recovery as Human Development: An assessment of the Streetscapes community-based rehabilitation programme - Bissolati, Chadley (Department of Sociology, 2023)
This study explores the experiences of previously homeless substance abusers who are part of Streetscapes, a community-based rehabilitation programme based in Cape Town, South Africa. The study aims to propose a different way of viewing addiction and recovery, where the focus is on the promotion of self-reliance and meeting people's needs in ways that are more holistic. The study was informed by a single case study design, which utilised qualitative research methods that included in-depth semi-structured interviews and document analysis. Data was analysed using the framework of Max-Neef's Human Scale Development (HSD) to conduct a needs-satisfier analysis of the programme from the perspective of its beneficiaries. The key findings indicate that participants are able to satisfy significantly more fundamental human needs (FHNs) as part of the Streetscapes programme, compared to when they were living on the street. More importantly, noticeably more synergic satisfiers were observed after joining the programme, thus highlighting Streetscapes' ability to foster self-reliance amongst its beneficiaries. The findings also revealed key challenges that need to be overcome to further promote self-reliance. The study argues that the promotion of self-reliance plays a major role with regards to one's recovery efforts. By focusing on the way in which people meet their FHNs, programmes are able to identify how their efforts provide opportunities for beneficiaries to satisfy their needs in ways that either promote or inhibit self-reliance. Thus, it is argued that an assessment of the Streetscapes programme from the perspective of beneficiaries' ability to meet their FHNs may allow it to be more effective in facilitating the process of recovery and promoting self-reliance amongst its beneficiaries. This research makes a contribution to debates in the literature about addiction, interventions for human development and recovery in relation to self-reliance, as well as the value of Max-Neef's Human Scale Development in the analysis of programmes and interventions aimed at helping homeless substance abusers.